Special Issue Forum: Navigating Privilege and Risk: Mothering and Professing During COVID-19. Issue 1 (2nd January 2022) - Blithe, Sarah Jane; Hughes, Jessica M. F.; Mercado Jones, Rebecca; Silverman, Rachel E.; Wolfe, Anna Wiederhold
Abstract: The novel coronavirus global pandemic—and the associated disease it causes (COVID-19)—swept the world in 2020, completely changing life as it once was. Academic mothers experienced COVID-19 as an unanticipated crash of simultaneous parenting responsibilities, remote teaching, and continued pressure to produce research. In this forum, four academic mothers present vignettes that represent their experiences navigating privilege and risk while parenting and professing during the COVID-19 pandemic.